Rare occurrence of central diabetes insipidus with dermatomyositis in a young male. (7th February 2020) - Ekhzaimy, Aishah; Masood, Afshan; Alzahrani, Seham; Al-Ghamdi, Waleed; Alotaibi, Daad; Mujammami, Muhammad
Abstract : Summary: Central diabetes insipidus (CDI) and several endocrine disorders previously classified as idiopathic are now considered to be of an autoimmune etiology. Dermatomyositis (DM), a rare autoimmune condition characterized by inflammatory myopathy and skin rashes, is also known to affect the gastrointestinal, pulmonary, and rarely the cardiac systems and the joints. The association of CDI and DM is extremely rare. After an extensive literature search and to the best of our knowledge this is the first reported case in literature, we report the case of a 36-year-old male with a history of CDI, who presented to the hospital's endocrine outpatient clinic for evaluation of a 3-week history of progressive facial rash accompanied by weakness and aching of the muscles. Learning points: Accurate biochemical diagnosis should always be followed by etiological investigation. This clinical entity usually constitutes a therapeutic challenge, often requiring a multidisciplinary approach for optimal outcome. Dermatomyositis is an important differential diagnosis in patients presenting with proximal muscle weakness. Associated autoimmune conditions should be considered while evaluating patients with dermatomyositis. Dermatomyositis can relapse at any stage, even following a very long period of remission. Maintenance immunosuppressive therapy should be carefully considered in these patients.